PENINGKATAN HASIL BELAJAR MAHASISWA DALAM MATERI MICROSOFT EXCEL PADA MATA KULIAH APLIKOM MELALUI METODE TUTOR SEBAYA PADA MAHASISWA FKIP PGSD UNSYIAH BANDA ACEH - Masyithah Masyithah (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2015)
This study was a classroom action research aimed to analyze the implementation of peer tutoring to improve students’ learning in Microsoft Excel and to assess students’ activity during the learning. The subjects were 32 students of Room 01 PGSD FKIP Unsyiah Banda Aceh. This study was conducted in three cycles each started with planning lesson plan, implementation of the lesson plan, observation of the lesson, and reflection. Students’ activities during the teaching and learning process were recorded using observation sheets. The scores ranged from low to excellent. Students’ achievements were assessed using an instrument designed by the team of researchers. The data obtained were then analyzed descriptively for each cycle. Result showed that in cycle I, the score for students’ activity was 1.4 (low) and then in cycle II the score was 2.3 (good). Finally in cycle III, the score was 3.5 (good). As for students’ achievement in cycle I, the average was 63.41 (C+) with only 1 student got an A, 9 students got a B, 16 students got a C+, 4 students got a C and 1 student got a D. In cycle II, the average was 68 (C+) with 1 student got a B+, 11 got a B, 19 got a C+, and 1 student got a C. In cycle III, the average was 78 (B+) with 3 students got an A, 12 students B+, and 17 students got a B.